TRANSFORMATION FROM CLASSICAL TEST THEORY (CTT) TO ITEM RESPONSE - EKPO, EFFIONG OJI; BASSEY, PROFESSOR S. W. (IJRDO- Journal of Educational Research, 2016)
The paper deals with the transformation from classical test theory (CTT) to item response theory (IRT) in research instrument validation. The paper recognizes the contribution of classical test theory (CTT) in sustaining the validation of psychological instruments. consequently upon the well – known pitfalls of the CTT and sometimes the misleading inferences arising from poorly validated and unreliable instrument, the study calls for a transformation from classical test theory (CTT) to item response theory (IRT) or at best an integration of both. The various methods of validation of IRT were discussed. It was recommended that IRT approaches should be vigorously taught to stakeholders and IRT software packages should be made more accessible to intended users